Thermodynamic calculation of LiH <-> Li3AlH6 <-> LiAlH4 reactions - Jang, Je-Wook; Shim, Jae-Hyeok; Cho, Young Whan; Lee, Byeong-Joo (ELSEVIER SCIENCE SA, 2006)
Thermodynamic properties of hydrides, LiH, Li3AlH6 and LiAlH4 which can be a promising candidate for a hydrogen storage material system, were critically assessed by analyzing available piecewise literature information on thermodynamic properties using the CALPHAD method. The optimized thermodynamic descriptions were used to compute the phase equilibria between Li3AlH6 and LiAlH4 as a function of temperature and hydrogen partial pressure. It was predicted that more than 10(3) bar of hydrogen partial pressure is necessary to induce the hydrogen absorption reaction of Li3AlH6 -> LiAlH4 above room temperature. It could be concluded that a reversible reaction between Li3AlH6 and LiAlH4 is thermodynamically impossible in a practically accessible temperature and hydrogen pressure range for a hydrogen storage material without any attempt to change the thermodynamic properties of the hydrides. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: HYDROGEN STORAGE; ALUMINUM; HYDRIDES; LIALH4; SYSTEM